Harmonization and qualification of an IFN-γ Enzyme-Linked ImmunoSpot assay (ELISPOT) to measure influenza-specific cell-mediated immunity within the FLUCOP consortium - Waerlop, Gwenn; Leroux-Roels, Geert; Lambe, Teresa; Bellamy, Duncan; Medaglini, Donata; Pettini, Elena; Cox, Rebecca Jane; Trieu, Mai-Chi; Davies, Richard; Bredholt, Geir; Montomoli, Emanuele; Gianchecchi, Elena; et al. (Frontiers in Immunology, 2022)
Influenza continues to be the most important cause of viral respiratory disease, despite the availability of vaccines. Today’s evaluation of influenza vaccines mainly focuses on the quantitative and functional analyses of antibodies to the surface proteins haemagglutinin (HA) and neuraminidase (NA). However, there is an increasing interest in measuring cellular immune responses targeting not only mutation-prone surface HA and NA but also conserved internal proteins as these are less explored yet potential correlates of protection. To date, laboratories that monitor cellular immune responses use a variety of in-house procedures. This generates diverging results, complicates interlaboratory comparisons, and hampers influenza vaccine evaluation. The European FLUCOP project aims to develop and standardize assays for the assessment of influenza vaccine correlates of protection. This report describes the harmonization and qualification of the influenza-specific interferon-gamma (IFN-ɣ) Enzyme-Linked ImmunoSpot (ELISpot) assay. Initially, two pilot studies were conducted to identify sources of variability during sample analysis and spot enumeration in order to develop a harmonized Standard Operating Procedure (SOP). Subsequently, an assay qualification study was performed to investigate the linearity, intermediate precision (reproducibility), repeatability, specificity, Lower and Upper Limits of Quantification (LLOQ-ULOQ), Limit of Detection (LOD) and the stability of signal over time. We were able to demonstrate that the FLUCOP harmonized IFN-ɣ ELISpot assay procedure can accurately enumerate IFN-ɣ secreting cells in the analytical range of 34.4 Spot Forming Units (SFU) per million cells up to the technical limit of the used reader and in the linear range from 120 000 to 360 000 cells per well, in plates stored up to 6 weeks after development. This IFN-ɣ ELISpot procedure will hopefully become a useful and reliable tool to investigate influenza-specific cellular immune responses induced by natural infection or vaccination and can be an additional instrument in the search for novel correlates of protection.